Deskrypcja różnic powierzchni plantokonturogramu między lewą a prawą stopą populacji dziewcząt w wieku od 4 do 18 lat, w ujęciu odsetkowym i w świetle mory projekcyjnej - Mrozkowiak, Mirosław (Journal of Education, Health and Sport, 2015)
Mrozkowiak Mirosław. Deskrypcja różnic powierzchni plantokonturogramu między lewą a prawą stopą populacji dziewcząt w wieku od 4 do 18 lat, w ujęciu odsetkowym i w świetle mory projekcyjnej = Description of the differences plantokonturogram space between the left and right foot population of girls aged 4 to 18 years, in terms of interest income and in the light moire projection. Journal of Education, Health and Sport. 2015;5(11):433-440. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34280 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A433-440 https://pbn.nauka.gov.pl/works/672963 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 24.11.2015. Deskrypcja różnic powierzchni plantokonturogramu między lewą a prawą stopą populacji dziewcząt w wieku od 4 do 18 lat, w ujęciu odsetkowym i w świetle mory projekcyjnej Description of the differences plantokonturogram space between the left and right foot population of girls aged 4 to 18 years, in terms of interest income and in the light moire projection Mirosław Mrozkowiak Uniwersytet Kazimierza Wielkiego, Bydgoszcz Mirosław Mrozkowiak Uniwersytet Kazimierza Wielkiego Bydgoszcz e-mail: magmar54@interia.pl strona: http://wadypostawy.republika.pl Słowa kluczowe: powierzchnia podeszwowa stopy, obciążenie masą ciała. Streszczenie Wstęp. Stopa spełnia węzłową rolę w lokomocji i motoryczności człowieka. Jej konstrukcja w postaci uformowanego sklepienia podłużnego i poprzecznego zapewnia odpowiednie amortyzowanie wszelkich obciążeń, nacisków i wstrząsów, utrzymuje ciało w pozycji spionizowanej, umożliwia poruszanie się, skakanie i bieganie. Cel. Określenie różnic powierzchni plantokonturogramów stóp w warunkach obciążenia masą własną, populacji żeńskiej w wieku od 4 do 18 lat w ujęciu odsetkowym. Materiał i metodyka. Badaniami objęto populację 9804 kobiet w wieku od 4 do 18 lat, z wybranych losowo przedszkoli i szkół regionu Warmińsko – Mazurskiego. Metodyka badań obejmowała pomiar powierzchni plantokonturogramu stóp (Gamma). Do oceny wykorzystano stanowisko do komputerowej oceny postawy ciała, techniką mory projekcyjnej – Posturometr M. Wyniki. Wyniki badań opracowano graficznie, przedstawiając przebieg zmian odsetka różnic powierzchni plantokonturogramu lewej i prawej stopy dla płci żeńskiej i obojga płci. Wnioski. 1. U dziewcząt o większej powierzchni plantokonturogramu lewej stopy odsetki różnic są większe niż u dziewcząt o większej powierzchni plantokonturogramu prawej stopy. 2. Wielkość odsetka różnic powierzchni stóp dziewcząt jest zbliżony do wielkości uzyskanych przez osobników obojga płci do 17 r.ż., dalej następuje gwałtowny wzrost wielkości różnic u osobników obojga płaci, posiadających większą powierzchnię plantokonturogramu lewej stopy. Keywords: plantar surface of the foot, the load weight. Abstract Admission. The rate meets the nodal role in human locomotion and motor skills. Its structure in the form of vault formed longitudinal and transverse provides adequate cushion any load, pressures and shocks, keeps the body in an upright position, to navigate, jumping and running. Objective. To determine the difference in interest plantokonturogram surface under load conditions unladen weight, the female population in age from 4 to 18 years in terms of interest income. Material and methods. The study population consisted of 9804 women aged from 4 to 18 years of randomly selected kindergartens and schools in the region of Warmia - Mazury. The research methodology consisted of measuring the area plantokonturogram feet (Gamma). Was used to evaluate the computed position to assess posture, technique of projection chamber - Posturometr M. Results. The results were processed graphically showing the percentage changes of surface differences plantokonturogram left and right foot for female and both sexes. Conclusions. 1. In girls with a larger surface area of the left foot plantokonturogram interest differences are greater than girls of greater area plantokonturogram right foot. 2. The size of the percentage differences in the surface of the feet of girls is similar to the size obtained by individuals of both sexes to 17 years of age, further rapid increase the size of the differences in individuals pay both having a larger surface plantokonturogram left foot.